The Application of Health Education and Pappasang in Promoting Adolescent Social and Emotional Development to Prevent Online Gaming Addiction - Nurmagandi, Boby; Damayanti, Risna (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Excessive online gaming in adolescents can lead to addiction, which may result in cognitive difficulties, social withdrawal, impaired concentration, anxiety, and depression. Preventive measures to prevent online game addiction in adolescents aim to optimize their essential social and emotional development. Preventive measures should provide health education focused on the psychosocial aspects of adolescent social and emotional growth, integrated with Pappasang, a traditional mandate passed down by the ancestors of the Mandar tribe. Unlike general advice, Pappasang emphasizes moral teachings that are expected to be followed. This study aims to evaluate the effect of health education and pappasang on optimizing adolescent psychosocial development. This study used a quasi-experimental method with a one-group pretest-posttest design. The population in this study were students SMAN 2 Majene Regency who regularly played online gaming over the past year. The sample in this study consisted of 57 respondents, selected through purposive sampling. Instruments used included an online gaming knowledge questionnaire, a strength and difficulties questionnaire, and an adolescent psychosocial development booklet on online gaming. Data analysis involved univariate analysis using measures of central tendency and a normality test (saphiro-wilk). Bivariate analysis was conducted using a non-parametric test, specifically Wilcoxon test and the marginal homogeneity test. The results indicated that health education combined with Pappasang effectively enhanced adolescents’ knowledge of social and emotional development, as well as their understanding of online gaming.  Social skills enable adolescents to engage in effective social interactions and seek social support when overcoming problems, while strong emotional skills help them manage their emotions in response to difficulties. Adolescents with well-developed social and emotional competencies are less likely to develop online gaming addiction, because they do not use online games as an escape from the their problems.